2010
DOI: 10.2118/137779-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recovery Technologies for the Grosmont Carbonate Reservoirs

Abstract: The Upper Devonian Grosmont Formation is a bitumensaturated, carbonate unit located in northern Alberta. It is considered to be one of the world's next largest unconventional oil resource plays. Since early 2006, there has been an increased interest in Grosmont resources exhibited by a range of companies including super-majors. Several in-situ pilot tests were conducted in the central portion of this area in the 1970s and 1980s utilizing steam and in-situ combustion processes. Similar to field tests in the McM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…The results from these tests were previously reported [9]. The results from these tests were previously reported [9].…”
Section: Simulation Studies On Warm Solvent Testmentioning
confidence: 86%
“…The results from these tests were previously reported [9]. The results from these tests were previously reported [9].…”
Section: Simulation Studies On Warm Solvent Testmentioning
confidence: 86%
“…A review by Edmunds et al (2009) showed that the high bulk permeability of fractured and vugular Grosmont Unit makes it an attractive target for steam recovery as well as non-thermal solvent technology based on gravity drainage. Warm solvent soak tests in laboratory on Grosmont cores, performed by Jiang et al (2010), showed nearly 50% bitumen recovery. A comparison of cyclic steam stimulation (CSS) in both Clearwater oil sands and Grosmont carbonates by Ezeuko et al (2012) indicated that the response of carbonates is completely different than that of oil sands and is very sensitive to the fracture network and steam injection pressure.…”
Section: Past Experience In Grosmontmentioning
confidence: 98%
“…Field and laboratory cold-solvent-soak experiments were performed to evaluate the cold-solvent potential for the Grosmont carbonates (Edmunds et al 2009). Recently, Jiang et al (2010) conducted one warm-solventsoak experiment with butane for a Grosmont carbonate core, and achieved a 50% recovery while keeping the experimental conditions at 50 C temperature and 400-kPa pressure. These conditions mean that butane was in the vapour phase (vapour pressure of butane at 50 C is approximately 500 kPa).…”
Section: Introductionmentioning
confidence: 99%